2015
DOI: 10.1186/s12906-015-0561-3
|View full text |Cite
|
Sign up to set email alerts
|

Samsoeum water extract attenuates allergic airway inflammation via modulation of Th1/Th2 cytokines and decrease of iNOS expression in asthmatic mice

Abstract: BackgroundSamsoeum has long been used in Korea and other Asian countries as a traditional medicine to treat various diseases. In the present study, we investigated the antiasthma effect of the herbal medicine Samsoeum water extract (SSEW) using an in vivo ovalbumin (OVA)-induced asthmatic model.MethodsFemale BALB/c mice were sensitized by an intraperitoneal injection of OVA and subsequently challenged with nebulized OVA. We investigated the number of inflammatory cells, the production of Th1/Th2 cytokines and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Attenuation of IFN- γ production may provide a therapeutic strategy to management these immune disorders. Several natural compounds from medicinal plants have been shown to possess therapeutic potentials for Th1-associated diseases (Jeon et al, 2015; Wu et al, 2014). The extracts of mushroom Phellinus igniarius were demonstrated to relieve the symptoms of EAE through inhibition of IFN- γ production and lymphocyte proliferation (Li et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Attenuation of IFN- γ production may provide a therapeutic strategy to management these immune disorders. Several natural compounds from medicinal plants have been shown to possess therapeutic potentials for Th1-associated diseases (Jeon et al, 2015; Wu et al, 2014). The extracts of mushroom Phellinus igniarius were demonstrated to relieve the symptoms of EAE through inhibition of IFN- γ production and lymphocyte proliferation (Li et al, 2014b).…”
Section: Discussionmentioning
confidence: 99%
“…To discover new botanicals with differential immunomodulatory effects on T-cell function may provide more therapeutics for different T-cell-mediated immune disorders. Many natural compounds isolated from medicinal plants have been shown to possess therapeutic potentials for Th1-associated diseases (Jeon et al, 2015; Wu et al, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…To induce asthma, OVA sensitization and airway challenge were performed as described previously [ 14 , 15 ]. The mice were sensitized on days 0 and 14 by intraperitoneal injection of 20 μg OVA emulsified in 2 mg aluminum hydroxide in 200 μL phosphate buffered saline (PBS) buffer (pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies applying HPLC‐UV and LC–MS methods have reported simultaneous quantification of SSE (Seo, Kim, Huang, & Shin, ; Weon, Yang, Lee, Ma, & Ma, ). Previous pharmacological studies have shown that SSE possesses immune‐regulating, adipogenesis‐attenuating, anticancer, and anti‐inflammation properties (Jeon, Shin, Shin, & Lee, ; Jeong, Yoo, Seo, & Shin, ; Kim et al, ; Kim, Yim, & Ma, ; Ryu et al, ). To date, SSE studies have focused on the development of analytical methods to assess its pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%